If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x-7=2(4-8x)
We move all terms to the left:
-x-7-(2(4-8x))=0
We add all the numbers together, and all the variables
-x-(2(-8x+4))-7=0
We add all the numbers together, and all the variables
-1x-(2(-8x+4))-7=0
We calculate terms in parentheses: -(2(-8x+4)), so:We get rid of parentheses
2(-8x+4)
We multiply parentheses
-16x+8
Back to the equation:
-(-16x+8)
-1x+16x-8-7=0
We add all the numbers together, and all the variables
15x-15=0
We move all terms containing x to the left, all other terms to the right
15x=15
x=15/15
x=1
| 2m–3=7 | | 5(3x-10)=23 | | 6+m=32 | | 4(4x-12)=24 | | 4x^=144+x^ | | 7x+10+3x-20=180 | | C=30+15n | | 2x+23=10x+10 | | 3x^=144 | | -2x+25=10x+9 | | 0,5x+0.5x=6 | | 3q-19=10q=23 | | 6+5a=36 | | 2x2+3x2+4=84 | | 21 x+83 =87 x+42 | | 2-(x+7)=14x+2 | | 2x2-3x2+4=3 | | 2+x=3x-10 | | 3(x-4=2(x-6) | | 3x18=18+36 | | 1/4+3/4a=-(7/4a-1) | | 2-(x+7)=14x=2 | | 2x2-3x2+4=-12 | | (4x-34)=(2x) | | x2/4+3=7 | | -5-4x=-10-9x | | 5{x+3}=30 | | 4x2-5=-1 | | 36-f=16 | | (2x+12)=(2x-64) | | 3x2+4=28 | | x/x=5/40 |